In memory of Wilhelm JORDAN - Board, Editorial (Archives of Acoustics, 1982)
Dr. Wilhelm Lassen Jordan, an outstanding Danish acoustician, a world-renowned expert in the field of interior acoustics, died, aged 72, on 3 February, 1982.